Ambulatory general urgent clinic: an initiative at the time of COVID-19 pandemic - Abdullah Al-Hothi (18505290) (2024)
Background In the ambulatory outpatients’ services, timely assessment of patients leads to earlier recognition of diseases and appropriate treatment. Long waiting time to get an appointment is a universal challenge that increased during the COVID-19 pandemic. The average waiting time to be seen for an urgent referral in our Department’s Physician Clinics is 14 to 21 days. Our quality improvement study aimed to decrease the waiting time by 20%, from 21 days in January 2021 to 14 days in April 2021, to evaluate the newly established clinics for urgent referrals during the COVID-19 pandemic, and to assess the physicians’ satisfaction regarding these clinics. Methodology New ambulatory general pediatric Urgent Clinics started in January 2021. The evaluation of the timing to book an urgent referral in clinics started by standardizing the process. The interventions to simplify the triaging and booking system are presented in Figure 1. Survey distributed among the physicians covering the clinics to discuss their perception for the newly implemented clinics and previous method to book urgent referral for in-person visits. Results 186 clinics were screened over 2 years (2 clinics per week). The average waiting time reduced from 21 days to 10 days (30%). 651 were booked as urgent patients. 73% of patients attended the clinics (Figure 1). 0.8% were referred directly to the Paediatric Emergency Centre and 5% were admitted to hospital from the clinics (Figure 2). The most frequent diagnosis were neurological disorders, cow milk allergy, and prolonged hyperbilirubinemia. Analysis of the urgent clinics’ attendance and physicians’ perceptions of clinics’ initiation are presented in Figure 2. Conclusion Waiting time is an important indicator of healthcare quality provided by any healthcare institution. Standardization of the urgent referral process played a major role in reducing patient waiting times for evaluation.